Potential ecological risk assessment of heavy metal contamination in surface sediment of the Siahrood River, Mazandaran province - Hassan Malvandi; Nasrin Hassanzadeh (Mashhad University of Medical Sciences, 2019)
Background and purpose: Evaluation of concentration and degree of heavy metal contamination in rivers based on sediment contamination indices is one of the important issues in ecotoxicology research. Therefore, the purpose of this study was to measure the heavy metal concentrations in the sediments of the Siahrood River and to assess the health risk of these pollutants. Another purpose was to determine the status of the river in terms of contamination and non-contamination for ecotoxicology studies. Materials and Methods: Acid digestion method was used to prepare the samples. Then the concentrations of Cr, Fe, Zn, As, Se, Ni, Co, Al and Mn were measured using ICP-OES. Pollution and ecological risk indices were also calculated. Results: The mean concentrations of chromium, iron, zinc, arsenic, selenium, nickel, cobalt, aluminum and manganese were 33.02, 7309.82, 42.61, 13.15, 13.36, 12.88, 6.58, 159.28 and 384.51 µg/g dw, respectively. Most of the studied elements were in the first category of pollution assessment indices. Conclusion: The results based on contamination indices and comparison with sediment quality guidelines showed that concentrations of Cr, Se and As are of concern and could potentially be a threat to the health of organisms. For ecotoxicology studies, this river is considered to be relatively contaminated in terms of Cr, Se and As and non-contaminated for other studied elements. However, further studies and monitoring of pollutants in this ecosystem are essential for making proper and effective management decisions.